(untitled) (American Journal of Arts and Human Science, 2024)
In the context of education, which is asynchronous and synchronous online learning, students’ persistence is of concern in most educational institutions. Several studies reveal many factors that influence students’ persistence. One of them is course satisfaction but hardly any research about the effect of psychological space of learners on students’ persistence. Thus, this study aimed to determine the mediating effect of transactional distance on the relationship between course satisfaction and student persistence. The study employed a descriptive-causal method of research and used an adaptive questionnaire that was contextualized by the researchers, and was participated by 239 senior high school students (grade 11 and grade 12) at the University of Mindanao Digos College; utilized stratified random sampling. The results of the study showed that the students are satisfied with their online course experience and thus students are highly likely to persist. Results also reveal that the transactional distance is low. Moreover, it also showed course satisfaction and student persistence are significantly related. However, after the insertion of transactional distance, the direct path unveiled insignificance while the indirect path revealed significant effect. Hence, the mediation analysis disclosed that transactional distance fully mediates the relationship between course satisfaction and student persistence. The paper provides evidence that in asynchronous and synchronous online learning, satisfaction should not solely be the focus in attaining students’ “intent-to-persist” but must also consider the perceived transactional distance of learners.